Measuring the performance of Islamic banks using maqāsid based model - Mohammed, Mustafa Omar; Tarique, Kazi Md; Islam, Rafikul (IIUM Press, 2015)
The vision and mission of Islamic banks were supposed to reflect the adherence of their activities and aspiration to Maqāṣid al-Sharī‘ah. However, there are contentions that Islamic banks have been converging towards conventional banking system. Efforts have been expended to reverse the tide and harmonise Islamic banking to its Sharī‘ah objectives. Hitherto,the existing conventional yardsticks have failed to measure the impact of the harmonisation exercise on Islamic banks’ performance. Therefore, using maqāṣid based yardstick to measure the performance of Islamic banks becomes imperative. This study has made use of al-Imām al-Ghazālī’s theory of Maqāṣid al-Sharī‘ah and Ibn ‘Āshūr’s reinterpretation, adopting content analysis and Sekaran (2000) behavioral science methods to develop a Maqāṣid Based Performance Evaluation Model (MPEM) to measure the performance of Islamic banks. Experts’ opinions have validated the model and its acceptability. Suggestions are provided to policy makers and future research.